Testing Factors Affecting the Remaining of Business Results in KPRI Ikhlas Kemenag City of Surakarta - Ari Susanti Susanti; Widyastuti Kurnia (Kusuma Negara Business School, 2020)
SHU of cooperative business is usually used as measure of the welfare of members. The greater the net income (SHU) obtained the welfare of the members will come true. There are several factors that influence to improve SHU such business volume, own capital, assets, and the number of members. This research is aimed to examine and analyzed of business volume, own capital total assets, and number of members on Time of Business Result (SHU) KPRI IKHLAS in Office Religion of Surakarta City. Methods of data collection using the entire financial annual report (RAT) on KPRI Ikhlas in 2011-2019. This study using SEM-PLS analysis with WarpPLS version 6.0 to analyzing the data. The results showed that: own capital (X1), total assets (X2), and number of members (X4) has positive and significant effect to SHU. Business volume (X3) don’t have significant effect on SHU.